Development of an Online Laguna Agricultural Trading Center - Jain, Archieval M.; Carandang, Charlotte B. (International Journal of Computing Sciences Research; Vol 2 No 4 (2018): Vol 2, No 4, 2018)
Purpose -  The purpose of the study is to develop a system that can be used as an alternative channel to improve the marketability of farm products of framers in Laguna. Method -  The proponent used two research methodologies. First is the software development which utilized the Agile Software Development. Second is the descriptive research which involved the determination of the acceptability of the software’s usability both by the farmers and the consumers. In this phase a combination of qualitative and quantitative methods was used. Results -  The proponent developed the Online Laguna Agricultural Trading Center. The system is an e-commerce website that will serve as an alternative channel of marketing the farmers’ products. It will also provide the farmer an easy and economical way of managing some of its business process.  Through its Short Message Service capability, the farmer can handle customer inquiries and update inventory of products and prices economically and easily. Based on evaluation, the farmers agreed, “it is easy to find information I needed”, while the buyer agreed that “the system is simple to use”. Conclusion -  Based on the findings, the proponent concluded that the developed system can be used as a channel to improve the marketability of farm products of farmers of Laguna. Recommendation -  Future researchers may look into the development of its own short messaging services that will not rely on third-party gateways. This will make its implementation less costly on the part of the Administrator. Adding of optional online payment transaction is also encouraged so that big farms who can afford to tie-up with payment centers may be able to do so. Implications -  E-commerce is not a new technology. However, there are no systems that directly resolved the problems of farmers. This paper reveals the real problems of farmers in the Philippines including their willingness to embrace technology that will improve their ability to gain income from their produce.